ANALISIS TRADISI MALAM BERINAI PADA PERKAWINAN PENDUDUK MELAYU DI DESA PAMBANG PESISIR MENURUT PERSPEKTIF HUKUM ISLAM - Armiyani, Armiyani; Wahida, Siti; Susanti, Triana (STAI Darul Qalam Tangerang, 2023)
Cultural diversity can be seen in the unitary state of the Republic of Indonesia. One of them is the cultural diversity that can be seen in wedding ceremonies in each region. Marriage is a custom that is customary, namely custom and individual, which can be exchanged for a copy. However, each traditional wedding ceremony is related to the spirit and social class of Malay life, and they can also be accepted as a whole in a different environment. Marriage is a procedure in which two human children are united in a sacred bond which has many purposes and benefits from different points of view. From a social perspective, for example, marriage is a way to strengthen relations between families and foster friendships both inside and outside the region. The night of henna is a ceremony where henna is given to the newlyweds before the newlyweds are performed the next day. In the evening after the Isha prayer, a bachelorette party is usually held. The night of henna is a very important part of the ceremony celebrating the newlyweds. The party only takes place at the bride's house. The henna night ceremony is not carried out at the groom's house. The groom receives henna from the bride sent by the bride. The groom greets his family. Giving bridal henna is an attempt to give signs and blessings from the family to the bride so that the bride can start a new household. In addition, henna is an expression of gratitude and prayer to Allah SWT so that the next day's wedding ceremony runs smoothly, free from all obstacles and obstacles